Efforts to Reduce Self-Injuring Behavior in Schizophrenia Patients in Online Clinical Practice Learning - Fabrila Hasti Endah Ramadani; Ice Yulia Wardani (Jurnal Ilmu Keperawatan Jiwa, 2020)
Self-injury is an action that can threaten the safety of patients with schizophrenia. During the Covid-19 pandemic, nursing care was provided through online practice learning. Self-injuring behavior experienced by a 23-year-old man with a medical diagnosis of Paranoid Schizophrenia. Clients have self-injury behavior when feeling depressed and depressed about the problems they are experiencing. The application of mental nursing care standards aims to set hope and the future, so that clients feel more optimistic about their lives. Nursing interventions include training in identifying positive aspects of oneself, family and environment, discussing hopes and the future and how to achieve them, and training activities to achieve the future. This scientific paper aims to analyze efforts to reduce self-injury in learning online clinical practice during the Covid-19 pandemic. The method used in this paper is a case report. The results of this research indicate that the client has decreased self-injury behavior after getting online nursing care. The successful application of nursing care standards to cilent is characterized by a change in the category of client self-injury from psychopathology to mild self-harm.